The General concept of human rights: international theoretical and legal aspects of development - Ж. Жайлау (Halyk̦aralyk̦ k̦atynastar ža̋ne halyk̦aralyk̦ k̦u̇k̦yk̦ seriâsì, 2016)
The purpose of this article is to examine the definitions in concept of human rights. The article deals with the international theoretical and legal aspects of human right`s development. The author conducted a comparative analysis of general human right`s development, their status and classifications. If you look at history of human right`s development, it is revealed that the human rights gone through several phases, which have their own characteristics. the modern catalogue of human rights stated in international law documents and the constitutions of the states of law, is the result of a long historical development of benchmarks and standards that have become the norm in the modern society.